The Role Of Imo Sign In The Life Of Children With Hearing Defects - Sattorova Dildora Mirzaakbarovna (Periodica Journal, 2024)
The article describes the use of sign language in the educational system of deaf children as a tool to help them understand the world around them, their upbringing using sign language in the family, and the fact that sign language is a communication tool for deaf children
Keywords: deaf child; gesture; word